Proceedings of the 8th ACM Conference on Embedded Networked Sensor Systems 2010
DOI: 10.1145/1869983.1869998
|View full text |Cite
|
Sign up to set email alerts
|

Meeting ecologists' requirements with adaptive data acquisition

Abstract: Ecologists instrument ecosystems to collect time series representing the evolution in time and space of relevant abiotic and biotic factors. Sensor networks promise to improve on existing data acquisition systems by interconnecting stand-alone measurement systems into virtual instruments. Such ecological sensor networks, however, will only fulfill their potential if they meet the scientists requirements. In an ideal world, an ecologist expresses requirements in terms of a target dataset, which the sensor netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Not all the data acquired by the users can be transmitted to the base station. In [7], the authors proposed ADAE, a utility-based controller that adaptively configures motes in a changing environment. ADAE presents three-tier architecture to organize the complexity of communicating with motes, representing the sensor network state and the user requirements, generating constraint optimization problems to determine the configuration parameters.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all the data acquired by the users can be transmitted to the base station. In [7], the authors proposed ADAE, a utility-based controller that adaptively configures motes in a changing environment. ADAE presents three-tier architecture to organize the complexity of communicating with motes, representing the sensor network state and the user requirements, generating constraint optimization problems to determine the configuration parameters.…”
Section: Related Workmentioning
confidence: 99%
“…Recent research works [5][6][7] have shown the abilities to reconfigure the parameters of sensors according to the changing environment. Usually, the control mechanism in these papers maintains its state based on the data obtained from the sensors and configures the remote devices with parameters that satisfy a constraint optimization problem derived from the current system state and the requirements of users.…”
Section: Introductionmentioning
confidence: 99%
“…By solving this COP we obtain a set of actions which adaptively changes the sampling strategy based on the scientist's requirements. For further details we refer the reader to [2].…”
Section: Autonomous Data Acquisitionmentioning
confidence: 99%
“…2 For ten years, a long-term monitoring program has focused on the water chemistry and occurrence of freshwater biota in two small lakes during summer. These measurements, however, do not adequately describe the processes in the lakes, especially not in the periods when the lakes are covered with ice.…”
mentioning
confidence: 99%
“…A broad range of application scenarios, e.g., [9,11,22,24], benefit from a minimum supported performance level that can be sustained over time periods on the order of multiple years. A system enhanced with energy harvesting capabilities canin theory -operate indefinitely as the energy store can be replenished periodically.…”
Section: Introductionmentioning
confidence: 99%